Religious Diversity in Muslim-majority States in Southeast Asia : Areas of Toleration and Conflict - Platzdasch, Bernhard; Saravanamuttu, J. (Jayaratnam) (Book collections on Project MUSE., 2014)
Volume and comparisons of contrasting developments in the two countries, challenges readers not to resort to easy conclusions and overgeneralizations about rising inter-religious tensions, but to give more scholarly attention to this politics-religion diversity nexus."--Emeritus Professor Francis Loh Kok Wah, Department of Political Science, Universiti Sains Malaysia.